2020
DOI: 10.1177/0300060520920411
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MACC1-AS1 promotes the stemness of hepatocellular carcinoma cells by antagonizing miR-145

Abstract: Objectives This work aimed to investigate the roles of long noncoding (lnc)RNA MACC1-AS1 (MACC1 antisense RNA 1) in progression of hepatocellular carcinoma (HCC). Methods Real-time quantitative PCR, western blot, spheroid formation, aldehyde dehydrogenase isoform 1 (ALDH1) activity analysis, luciferase reporter assay, and RNA pull-down analysis were used to examine MACC1-AS1–mediated effects on HCC cell stemness. Results MACC1-AS1 was highly expressed in HCC tissues and cells. MACC1-AS1 positively regulated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Some lncRNAs were confirmed to be aberrantly expressed and to participate in the pathophysiology of ischemic stroke (12,13), and in the present study, lncRNA MACC1-AS1 was found to be downregulated in hypoxia-induced vascular endothelial cells. LncRNA MACC1-AS1 has been identified as an oncogene in hepatic carcinoma, lung adenocarcinoma, pancreatic carcinoma, gastric cancer, and other cancers (19,(28)(29)(30), but its role in other diseases remains relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Some lncRNAs were confirmed to be aberrantly expressed and to participate in the pathophysiology of ischemic stroke (12,13), and in the present study, lncRNA MACC1-AS1 was found to be downregulated in hypoxia-induced vascular endothelial cells. LncRNA MACC1-AS1 has been identified as an oncogene in hepatic carcinoma, lung adenocarcinoma, pancreatic carcinoma, gastric cancer, and other cancers (19,(28)(29)(30), but its role in other diseases remains relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…MACC1-AS1, a homologous antisense lncRNA for the sixth intron of the MACC1 gene, has been linked to the development of certain malignancies through influencing miRNAs, according to numerous studies. MACC1-AS1 promotes proliferation by downregulating PTEN in lung adenocarcinoma cells [ 97 ], promoting invasion and proliferation by regulating paired-box gene 8 (PAX8) in hepatoma cells [ 98 ], promoting stemness by antagonizing miR-145 [ 99 ], and upregulating cyclin-dependent kinase 6 in cervical squamous cell carcinoma [ 100 ]. In pancreatic cancer, it promotes cancer progression by activating the PAX8/NOTCH1 signaling pathway [ 101 ].…”
Section: Macc1-as1 Participates In Bc’s Cerna Regulatory Networkmentioning
confidence: 99%
“…LncRNA LINC00460 regulates liver cancer cell proliferation by targeting the miR-503-5p/miR-654-3p/TCP1 axis ( 118 ). Long noncoding RNA MACC1-AS1 promotes ALDH1 in stem cells from hepatocellular carcinoma by antagonizing miR-145 ( 119 ). Carboxypeptidase A4 upregulates ALDH1 expression and promotes proliferation of hepatocellular carcinoma ( 120 ).…”
Section: Aldh1 and Various Solid Tumorsmentioning
confidence: 99%